Application of Profile Matching in Determining Employee Annual Bonuses - Puspa Dewi, Nindian; Ramadhani, Nilam; Darmawan, Irwan; Ubaidi, Ubaidi; Syahroni, Abd Wahab (SEULANGA SYSTEM PUBLISHER, 2024)
In the competitive business world, companies are required to have an effective and objective performance appraisal system. One crucial aspect of employee performance appraisal is the annual bonus distribution. One effort to improve employee performance is by providing annual bonuses. For this reason, currently, many companies are implementing this bonus so that their employees are motivated to improve and increase the quality of their work. One of them is a CV. Laras Alam Pamekasan. CV. Laras Alam Pamekasan is a company operating in the tobacco sector specifically supplying PT. Djarum Tobacco. Every year, CV. Laras Alam provides annual bonuses according to employee performance. However, bonuses are still based on rough calculations. That's why research was conducted to produce a decision support system in determining employee annual bonuses based on performance. This research uses the Profile Matching method. Profile Matching is one method in performance appraisal systems that uses a comparative approach between employee profiles and predefined ideal profiles. The aspects used in determining employee annual bonuses are the Work Attitude Aspect including criteria, behavior, responsibility, and cooperation. Performance Aspects include criteria, discipline, absenteeism, acceptance of additional assignments, and loyalty. From this research, a trial was carried out on 22 employees and then calculations and rankings were carried out.